2002
DOI: 10.1094/phyto.2002.92.5.464
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathogenic Isolates of the Citrus Black Spot Fungus, Guignardia citricarpa, Identified as a Cosmopolitan Endophyte of Woody Plants, G. mangiferae (Phyllosticta capitalensis)

Abstract: The population structure of Guignardia citricarpa sensu lato (anamorph: Phyllosticta citricarpa), a fungus of which strains pathogenic to citrus are subject to phytosanitary legislation in the European Union and the United States, was investigated. Internal transcribed spacer sequences revealed two phylogenetically distinct groups in G. citricarpa. This distinction was supported by amplified fragment length polymorphism analysis that also supported the exclusion of two isolates that had apparently been misclas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
192
1
22

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 183 publications
(231 citation statements)
references
References 10 publications
16
192
1
22
Order By: Relevance
“…The fragments were then placed on potato dextrose agar (PDA) and incubated at 25ºC until colonies were found that were characteristic for Phyllosticta species. Subcultures were transferred to oatmeal agar (OA) and colonies were checked for a yellow halo to distinguish P. citricarpa from P. capitalensis (Baayen et al, 2002). Morphology and size of conidia were checked microscopically (Wikee et al, 2011).…”
Section: Phyllosticta Isolates Usedmentioning
confidence: 99%
See 4 more Smart Citations
“…The fragments were then placed on potato dextrose agar (PDA) and incubated at 25ºC until colonies were found that were characteristic for Phyllosticta species. Subcultures were transferred to oatmeal agar (OA) and colonies were checked for a yellow halo to distinguish P. citricarpa from P. capitalensis (Baayen et al, 2002). Morphology and size of conidia were checked microscopically (Wikee et al, 2011).…”
Section: Phyllosticta Isolates Usedmentioning
confidence: 99%
“…However, strains that have been described as G. mangiferae do not always have P. capitalensis as anamorph (Glienke et al, 2011). P. capitalensis has been found on CBS affected citrus trees as well as healthy and asymptomatic trees, and has a wider host range than P. citricarpa extending beyond the Rutaceae, commonly as an endophyte (Baayen et al, 2002;Bezerraet al, 2012;Everett & Rees-George, 2006;Glienke et al, 2011;Johnston, 1998;Okane et al, 2001;Rakotoniriana et al, 2008;Rodrigues & Samuels, 1999;Rodrigues et al, 2004;Yuan et al, 2009). Guignardia mangiferae sensu stricto (not necessarily P. capitalensis) is a pathogen of mango (Mangifera indica L), but is nonpathogenic to other species (Baldassari et al, 2008;Glienke et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations